Peran modal sosial sebagai solusi konflik pasca gempa bumi - Yusuf Ratu Agung; Yahya yahya; Rika Fuaturosida; M. Naufal Firosa Ahda; Khusnul Khotimah; Syamsul Hidayat (UIN Maulana Malik Ibrahim Malang, 2022)
ABSTRACTThe potential for post-disaster conflict often occurs in affected communities. Especially in the process of distributing incoming donations to each affected area. This study raises the topic of potential conflicts that arise after the earthquake in Malang. The conflicts that arise are motivated by several factors and their dynamics. In addition to the potential for post-earthquake conflict, this research tries to present a solution with the role of local community social capital in conflict resolution. The social capital found in the field is the value of harmony, racket, and mutua cooperation. The method used in this research is to use the theoretical framework of motives, incentives, and opportunities. The results of the study indicate that the potential for post-disaster conflict is based on the mental condition of the community which is still unstable and economic factors that are less stable due to the disaster. Thus, collaboration between the role of the stakeholder and social capital is needed to help earthquake survivors for surviving.KEY WORDSDisaster; Conflict; Social CapitalABSTRAKPotensi konflik pasca bencana kerap terjadi dalam masyarakat terdampak, Khususnya pada proses pendistribusian bantuan donasi yang masuk pada setiap daerah terdampak. Penelitian ini mengangkat topik terkait potensi konflik yang muncul pasca bencana gempa di Malang. Konflik yang timbul dilatar belakangi oleh beberapa faktor dan dinamikanya. Selain potensi konflik pasca gempa, penelitian ini berusaha menampilkan solusi dengan peranan modal sosial masyarakat setempat dalam penyelesaian konflik. Modal sosial yang ditemukan di lapangan yaitu nilai rukun, raket, dan gotong royong. Metode yang digunakan dalam penelitian ini berupa kualititaif dengan pendekatan studi kasus. Dari hasil penelitian menunjukkan timbulnya potensi konflik pasca bencana didasari pada kondisi masyarakat secara mental yang masih labil dan faktor ekonomi yang kurang stabil akibat bencana. Dengan demikian kolaborasi anatara peran stackholder dan modal sosial sangat dibutuhkan untuk membantu penyintas gempa bangkit kembali.KATA KUNCIBencana; Konflik; Modal Sosial